2016
DOI: 10.1063/1.4940795
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved photoelectron spectroscopy of a dinuclear Pt(II) complex: Tunneling autodetachment from both singlet and triplet excited states of a molecular dianion

Abstract: Time-resolved pump-probe photoelectron spectroscopy has been used to study the relaxation dynamics of gaseous [Pt2(μ-P2O5H2)4 + 2H](2-) after population of its first singlet excited state by 388 nm femtosecond laser irradiation. In contrast to the fluorescence and phosphorescence observed in condensed phase, a significant fraction of the photoexcited isolated dianions decays by electron loss to form the corresponding monoanions. Our transient photoelectron data reveal an ultrafast decay of the initially excite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…This species exhibits the same absorption bands as Pt(pop) in solution, suggesting very similar energetics of the lowest triplet and singlet states, but also of the higher-lying UV bands. Ultrafast experiments (67) showed that the S 1 state undergoes a decay accompanied by a concomitant rise in population of the T 1 state with the same rate as the ISC in MeCN. While this may be fortuitous, it does raise an in-teresting question.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This species exhibits the same absorption bands as Pt(pop) in solution, suggesting very similar energetics of the lowest triplet and singlet states, but also of the higher-lying UV bands. Ultrafast experiments (67) showed that the S 1 state undergoes a decay accompanied by a concomitant rise in population of the T 1 state with the same rate as the ISC in MeCN. While this may be fortuitous, it does raise an in-teresting question.…”
Section: Resultsmentioning
confidence: 96%
“…Pt(pop) is unstable in the gas phase, but the protonated [Pt(pop) + 2H] 2− anionic species is stable and was recently characterized by mass spectrometry and time-resolved pump-probe photoelectron spectroscopy (66,67). This species exhibits the same absorption bands as Pt(pop) in solution, suggesting very similar energetics of the lowest triplet and singlet states, but also of the higher-lying UV bands.…”
Section: Resultsmentioning
confidence: 99%
“…The Ag 29 (BDT) 12 (TPP) 4 solid was synthesized following a previously reported method and used without further purification . Approximately 5 μM of clusters in dimethylformamide (DMF) was electrosprayed and probed using an ion beam apparatusparts of which have been previously described. It has recently been modified to incorporate a velocity map imaging (VMI) setup and a new femtosecond laser system.…”
mentioning
confidence: 99%
“…Here we show how hard X-ray Free Electron Laser (XFEL) sources [13] now make it possible to directly map the structural dynamics of an ensemble of molecules as it evolves on the ground-state potential surface. illustrating this approach we investigate how the ground-state population of the much-studied di-platinum anion Pt- (Figure 1) [14][15][16][17][18][19][20][21][22][23] evolves following Pt-Pt distance-dependent photo-depletion of the ground-state population.…”
mentioning
confidence: 99%